Polypharmacy — an important issue in elderly patients care - Biercewicz, Monika; Szrajda, Justyna; Haor, Beata; Kędziora-Kornatowska, Kornelia (Nursing Problems / Problemy Pielęgniarstwa, 2012)
With the demographic changes taking place in Poland and other European countries, it is reasonable to pay particular attention to the health situation and problems that occur in elderly patients. The article focuses on polypharmacy, resulting from polypathology in elderly patients, which seems to be a major problem both in terms of health and economy. The authors also discuss the most important rules of conduct during pharmacological treatment in the elderly with respect to the nursing actions and the role of geriatric nurses.